Furano-1, 2-Naphthoquinone Inhibits Src and PI3K/Akt Signaling Pathways in Ca9-22 Human Oral Squamous Carcinoma Cells. (May 2014) - Lin, Kuei-Li; Chien, Ching-Ming; Tseng, Chih-Hua; Chen, Yeh-Long; Chang, Long-Sen; Lin, Shinne-Ren
Furano-1, 2-naphthoquinone (FNQ), a biologically active component of Avicennia marina, has been demonstrated to display anticancer activity. FNQ exerted cytotoxicity with the G2 /M cell cycle arrest and apoptosis in Ca9-22 cells. FNQ-induced G2 /M arrest was correlated with a marked decrease in the expression levels of cyclin A and cyclin B, and their activating partner cyclin-dependent kinases (CDK) 1 and 2 with concomitant induction of p27. FNQ-induced apoptosis was accompanied by Bax and Bad upregulation, and the downregulation of Bcl-2, Bcl-XL, Mcl-1, and X-linked inhibitor of apoptosis (XIAP), resulting in cytochrome C release and sequential activation of caspase-9 and caspase-3. Mechanistic studies showed that FNQ suppressed Src phosphorylation, PI3K, and Akt activation in Ca9-22 cells. Moreover, the Src inhibitor PP2 reduced the phosphorylation of Src and activation of PI3K/Akt, which was comparable with FNQ treatment. The combined treatment of FNQ with PP2 enhanced the cell cycle arrest and apoptosis and also led to the downregulation of Bcl-XL, Mcl-1, XIAP, cyclin A, cyclin B, CDK1, and CDK2 and upregulation of p27, Bax, and Bad. These findings suggest that FNQ-mediated cytotoxicity of Ca9-22 cells is related with the G2 /M cell cycle arrest and apoptosis via inactivation of Src and PI3K/Akt–mediated signaling pathways.